(untitled) (Anuário Antropológico, 2023)
More than five years ago, when the author began to draft this text, in which I participated as one of her interlocutors, our contact, just started, became a student-advisor relationship for my doctoral research. Back then, we began to discuss the issue of indigenous scholars entering anthropology through its front door as students in graduate programs, seeking a degree and anthropological expertise.